2006
DOI: 10.1016/j.cub.2006.05.051
|View full text |Cite
|
Sign up to set email alerts
|

STIM2 Is an Inhibitor of STIM1-Mediated Store-Operated Ca2+ Entry

Abstract: The coupling mechanism between endoplasmic reticulum (ER) Ca(2+) stores and plasma membrane (PM) store-operated channels (SOCs) remains elusive [1-3]. STIM1 was shown to play a crucial role in this coupling process [4-7]; however, the role of the closely related STIM2 protein remains undetermined. We reveal that STIM2 is a powerful SOC inhibitor when expressed in HEK293, PC12, A7r5, and Jurkat T cells. This contrasts with gain of SOC function in STIM1-expressing cells. While STIM1 is expressed in both the ER a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
240
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(260 citation statements)
references
References 17 publications
16
240
3
1
Order By: Relevance
“…Indeed, basal calcium levels declined in the presence of Stim2 siRNA-mediated inhibition in HC11 mammary cells. A modest, rather than an order or magnitude increase, in STIM2 levels during lactation would avoid the potential inhibitory effects of STIM2 on ORAI1 activity (38), which occurs with sustained high STIM2 overexpression (35). It is likely that the relative levels of STIM1, STIM2, and ORAI1 are important in the context of the physiological environment, as the expression levels of STIM1 and ORAI1 dictate the nature of the channel current (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, basal calcium levels declined in the presence of Stim2 siRNA-mediated inhibition in HC11 mammary cells. A modest, rather than an order or magnitude increase, in STIM2 levels during lactation would avoid the potential inhibitory effects of STIM2 on ORAI1 activity (38), which occurs with sustained high STIM2 overexpression (35). It is likely that the relative levels of STIM1, STIM2, and ORAI1 are important in the context of the physiological environment, as the expression levels of STIM1 and ORAI1 dictate the nature of the channel current (49).…”
Section: Discussionmentioning
confidence: 99%
“…5A). Given the report of opposing effects of STIM1 and STIM2 on ORAI1-mediated calcium influx (38), the ratio of the expression of these 2 genes was compared in breast cancer cell lines. The comparison between the relative levels of STIM1 and STIM2 indicated that the relative levels of STIM1 to STIM2 were similar in the breast cancer cell lines, with the exception of the ERBB2 overexpressing cell line SK-BR-3 (Fig.…”
Section: Stim1 and Stim2 And Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, STIM1 and STIM2 are known to form heterodimers (Williams et al, 2001;Soboloff et al, 2006;Darbellay et al, 2010), which could provide a mechanism to recruit STIM2β to Orai channels and facilitate inhibition. We used a FRET assay to assess the ability of STIM2β to heterodimerize with STIM1.…”
Section: Heterodimerization With Stim1 Recruits Stim2β To Orai1 Channelsmentioning
confidence: 99%
“…STIM1 is an acknowledged activator of store-operated Ca 2+ entry and CRAC channel function as discussed below, but the role of STIM2 was initially controversial, with conflicting results reported by different groups [36,37,43]. An important clue as to the possible distinction between the two proteins came when STIM2 showed up as a major hit in an RNAi screen designed to find regulators of basal Ca 2+ concentration, which is kept within very narrow limits in cells [••44].…”
Section: Store-operated Ca 2+ Entry Through Crac Channels: Stim and Oraimentioning
confidence: 99%